2017
DOI: 10.2147/rrcc.s132126
|View full text |Cite
|
Sign up to set email alerts
|

Uncontrolled hypertension and associated factors among adult hypertensive patients on follow-up at Jimma University Teaching and Specialized Hospital: cross-sectional study

Abstract: Introduction: Hypertension, including poorly controlled blood pressure, is the major global health problem that affects one billion people worldwide. Limited studies have been conducted on prevalence of uncontrolled hypertension and associated factors among adult hypertensive patients in Ethiopia. Objective: The aim of this study was to determine the prevalence of uncontrolled hypertension and associated factors among adult hypertensive patients at Jimma University Teaching and Specialized Hospital. Methods: I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
59
5
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(87 citation statements)
references
References 24 publications
17
59
5
6
Order By: Relevance
“…Compared to another study in Ethiopia, the current study was almost lower than in Jimma specialized hospital in (2016) (17), in Gonder hospital in (2012) (18), and in Adama hospital in (2014) (19) which were 52.7%, 53.4% and 56.4% respectively. This variation might be due to environmental factors and this may overestimate the magnitude.…”
Section: Discussioncontrasting
confidence: 81%
“…Compared to another study in Ethiopia, the current study was almost lower than in Jimma specialized hospital in (2016) (17), in Gonder hospital in (2012) (18), and in Adama hospital in (2014) (19) which were 52.7%, 53.4% and 56.4% respectively. This variation might be due to environmental factors and this may overestimate the magnitude.…”
Section: Discussioncontrasting
confidence: 81%
“…In the current study, the overall prevalence of uncontrolled hypertension was 56.83%. In comparison to other studies conducted in Africa, the figure presented in this study was slightly lower than those reported in Zimbabwe (61.0%) [25] and Nigeria (60.0%) [26], but higher than the 52.7% reported in Ethiopia [27]. In comparison to other studies conducted in different parts of South Africa, the result is lower than the 75.5% that was reported in the rural Eastern Cape province [12]; however, higher than the 13.5% prevalence that was reported in the South African National Health and Nutrition Examination Survey [14].…”
Section: Discussioncontrasting
confidence: 94%
“…In the current study, the presence of obesity was significantly associated with uncontrolled hypertension. These findings are supported by studies conducted in Ethiopia [13,27], China [28] and Zimbabwe [29], where excessive body weight was statistically associated with the incidence of uncontrolled hypertension [28,29]. Moreover, it has been shown that a modest weight-loss will not only decrease blood pressure, but will also have a favourable impact on obesity related risk factors [29,30].…”
Section: Discussionmentioning
confidence: 64%
“…Diperkirakan lebih dari 50% pasien hipertensi tidak patuh terhadap obat/rejimen yang ditentukan sebelumnya. 15 Distribusi pasien gagal jantung akut berdasarkan fraksi ejeksi ialah 50-70% pada 35 pasien (39,3%), 40-49% pada 17 pasien (19,1%), dan <40% pada 37 pasien (41,6%). Brigham and Women's Hospital dengan pemeriksaan ekokardiografi melaporkan bahwa dari 908 pasien didapatkan 620 pasien dengan fraksi ejeksi <40 %.…”
Section: Bahasanunclassified